Pengaruh Konsep Diri Terhadap Gaya Hidup Hedonisme Mahasiswa - Ramadani, Astri; Marhani, Marhani; Suarja, Septya (Yayasan Pendidikan Riset dan Pengembangan Intelektual (YRPI), 2024)
This research aims to find out whether self-concept can influence students' hedonistic lifestyles. A hedonistic lifestyle characterized by excessive consumption, chasing instant gratification, and ignoring long-term values is increasingly common among students. This phenomenon raises questions about the factors underlying this hedonistic lifestyle. One interesting factor to observe is self-concept. This type of research uses quantitative methods with a correlational research design. The technique used for this research is purposive sampling. The population in this research is active students of the Guidance and Counseling study program, totaling 150 students and the sample for this research is 97 people. The data collection technique uses a questionnaire that has been adapted using a Likert scale. The data analysis technique uses simple linear regression analysis. The results of the research show that the calculated t value (5.354) > t table value (1.661), and the significance value (0.000) < 0.05, then the null hypothesis (H?) is rejected and the alternative hypothesis (H?) is accepted, so that the self-concept variable has a significant effect on hedonistic lifestyle. This research provides a valuable contribution in understanding the influence between self-concept and hedonistic lifestyle. However, it is important to remember that the results of this study have limitations and need to be interpreted with caution.